THE EFFECT OF READING INYETERST AND GRAMMAR MASTERY TOWARD THE STUDENTS’ READING SKILLS OF THE PRIVATE SENIOR HIGH SCHOOL IN EAST JAKARTA - Sumardjo . (Journal Of Communication Education, 2019)
ABSTRACTThis research is aimed at finding the effect of reading interest and grammar mastery toward thestudents’ reading skill. The hypothesis of the study includes: 1). There is a collaborative significanteffect of reading interests and grammar mastery toward the students’ reading skill; 2). There is asignificant effect of reading interests toward the students’ reading skill; and 3). There is asignificant effect of the grammar mastery toward the students’ reading skill. The method of theresearch is a descriptive survey using some samples from a number of population and using testsinstrument for data collection. The number of the samples is six (6) classes from three (3) schoolsnamely THE BUDI WARMAN 1 SENIOR HIGH SCHOOL, THE BUDI WARMAN 2 SENIORHIGH SCHOOL, and THE MALAHAYATI SENIOR HIGH SCHOOL East Jakarta. The result ofthe research shows that; 1). There is a collaborative significant effect of the reading interests andthe grammar mastery toward the students’ reading skill of Private Senior High School in EastJakarta. The significant effect was proved by the score of Sig. = 0,000 < 0,05 and F0 = 18.056.Both variables, the reading interests and the grammar mastery had given a contribution of 31,1%to the students’ reading skill. 2). There is significant effect of the reading interests toward thestudents’ reading skill of the Private Senior High school in East Jakarta. The significant effect wasproved by the score of Sig. = 0,009< 0,05 and t0 = 2.669. The reading interests had given acontribution to the students’ reading skill of 10.55%. 3). There is a significant effect of thegrammar mastery toward the students’ reading skill of the Private Senior High school students inEast Jakarta. The significant effect was shown by the score of Sig. = 0,000 < 0,05 and t0= 4,173.This variable had given a contribution to the students’ reading skill of 20,55%.Key words: Reading Interest, Grammar Mastery, Reading skill.